Cardamine mangshanensis, a new species of Brassicaceae from limestone landform in Southern Hunan, China - Ang Liu; Xiong Li; Guo-xing Deng; Jun Chen; Zan Liu; Xun-Lin Yu; Lei Wu (PhytoKeys)
Cardamine mangshanensis, a new species, is described and illustrated from the limestone landform in southern Hunan, China. The new species is similar to C. macrophylla, but differs from the latter in having more prominent tubers, shorter plant height (10–25 cm vs. 30–95 cm), fewer cauline leaves (3–4 vs. 3–18), crenate leaf margin (vs. serrate), fewer flowers (4–10 vs. 10–30), an earlier flowering period (late February to mid-March vs. April to June) and a shorter growth cycle (ca. 4 months vs. ca. 8 months). Following the IUCN Red List Criteria, C. mangshanensis is assessed as ‘Vulnerable, VU B2ab(ii)’.